Penentuan Keandalan Sistem Distribusi 20 KV Penyulang Malili dengan Metode Section Technique dan FMEA - Usman, Usman; Indra, Indra; Thahir, Muhammad; Sofyan, Sofyan; Idris, Ahmad Rosyid; Thaha, Sarma (PROtek : Jurnal Ilmiah Teknik Elektro, 2022)
This paper discusses the determination of the reliability index of the power distribution system. The reliability of the power distribution system is strongly influenced by the duration and frequency of the disturbance, causing customers not to receive electrical energy. This reliability is measured by indices called SAIFI, SAIDI, and CAIDI. The method used to calculate the failure rate required to determine the reliability indexes are the section technique and Failure Mode Effect Analysis (FMEA). The results obtained using the FMEA method are better results. Compared to PLN's SAIFI and SAIDI standards, the Malili feeder is still quite reliable, because its value is smaller than the PLN standard. However, when compared to the IEEE standard, this Malili feeder is not categorized as reliable because the SAIFI value obtained is still higher. While for SAIDI the value is still below the IEEE standard. To improve the reliability index of this feeder, it is necessary to add a protection component to localize the fault.